Utilizing Fe(III)/(II)-EDTA Couple for Estimation of Transition Metal Ion Mixture Over Platinum Electrode - Ahmad Rizvi, Masood; Teshima, Norio; Mustafa Peerzada, Ghulam (Asian Journal of Chemistry, 2013)
The work describes an indirect estimation of some transition metal ions and their binary mixture over platinum electrode by generating Fe(III)/(II)-EDTA redox couple in solution. This approach offers easy estimation and can allow replacement of costly and delicate ion selective electrodes with simple platinum electrode within the limits of concentration and tolerable margin of error.